THE INNOVATION CODE : THE CREATIVE POWER OF CONSTRUCTIVE CONFLICT - DeGraff, Jeffrey Thomas, author; DeGraff, Staney, author (Oakland, CA : Berrett-Koehler Publishers, Inc., 2017)
From years of research and practical experience as a consultant, Jeff DeGraff has learned that when it comes to any innovation initiative, disharmony is crucial. We innovate when we disrupt, and we first have to disrupt each other. DeGraff identifies four contrasting types of innovators. There's the wild experimentation of The Artist, the pragmatic caution of The Engineer, the urgent competitiveness of The Athlete, and the patient community-building of The Sage. He includes exercises so readers can find where they fit into this framework, and shows how to build, manage, and embrace the dynamic discord of a team that contains all four types. When you combine the visionary thinking of The Artist and the practical thinking of The Engineer, you get innovation that's both revolutionary and manageable, highly ambitious without high risk. When you combine the results-oriented attitude of The Athlete with the values-oriented attitude of The Sage, you get innovation that's both a good investment and good for the world. This is a profound but highly accessible guide for achieving breakthrough solutions by utilizing the full--and seemingly contradictory--spectrum of innovative thinking